Design of a web-based personality profiling assessment system - Li, Weini (2014)
Individuals require a self-awareness of their personality traits in order to empower them in their career. However, analytical tools which can scientifically and statistically predict their behaviours could be marketed to them with greater reach. There is a need to develop these precise tools to enable individuals to succeed better using a systematic analysis of themselves.